How to do critical discourse analysis : a multimodal approach - Mayr, Andrea , 1972- (Sage Publications, 2012)
How do media texts manipulate and persuade us? How do language and images play out the ideas, values and identities? This book shows readers exactly how language, power and ideology are negotiated in media texts, from magazine and advertising, to YouTube and music videos. Presenting a systematic toolkit of theories, concepts and techniques for doing language and image analysis, students learn how to dig deep into discourses and the media landscape. With case studies and examples from a range of traditional and new media content